THE INVISIBLE BURDEN: A COMPREHENSIVE REVIEW OF PSYCHOLOGICAL ASPECTS IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Maciej Sulerzycki; Katarzyna Pomykała (International Journal of Innovative Technologies in Social Science, 2026)
Ankylosing Spondylitis (AS) is a chronic, inflammatory rheumatic disease primarily affecting the axial skeleton. While the physical manifestations are well-documented, the psychological burden is often under-recognized. This comprehensive review aims to synthesize current evidence on the prevalence, etiology, and impact of psychological comorbidities, particularly depression, anxiety, and reduced health-related quality of life (HRQoL), in patients with AS. A systematic literature search was conducted in PubMed, Scopus, and Web of Science databases for articles published between 2000 and 2024. Search terms included "ankylosing spondylitis," "psychology," "depression," "anxiety," "quality of life," "fatigue," "sleep," and "coping." Studies were included if they focused on adult human subjects with AS and assessed psychological outcomes. The reviewed literature consistently demonstrates a high prevalence of psychological distress in AS, with pooled estimates of depression and anxiety significantly higher than in the general population. Key factors contributing to this burden include chronic pain, fatigue, sleep disturbances, functional limitations, and disease activity. Furthermore, psychological factors, such as catastrophizing and passive coping strategies, are identified as significant mediators of pain perception and disability. The bidirectional relationship between psychological state and disease activity creates a vicious cycle that adversely affects treatment adherence and overall prognosis. Psychological comorbidity is a prevalent and debilitating aspect of AS that warrants systematic screening and integrated management. A multidisciplinary approach, combining pharmacological therapy with psychological interventions (e.g., Cognitive-Behavioral Therapy) and physical rehabilitation, is essential to address the biopsychosocial complexity of the disease and improve patient outcomes.